Editorial: infliximab or adalimumab as first‐ or second‐line anti‐TNF—conflicting evidence—authors' reply. Issue 6 (23rd August 2021) - Visuri, Isabella; Eriksson, Carl; Olén, Ola; Cao, Yang; Mårdberg, Emelie; Grip, Olof; Gustavsson, Anders; Hjortswang, Henrik; Karling, Pontus; Montgomery, Scott; Myrelid, Pär; Ludvigsson, Jonas F.; et al.
LINKED CONTENT: This article is linked to Visuri et al and Haydek & Scott papers. To view these articles, visit https://doi.org/10.1111/apt.16525 and https://doi.org/10.1111/apt.16555